2017
DOI: 10.1021/acs.nanolett.7b04369
|View full text |Cite
|
Sign up to set email alerts
|

A Nanobionic Light-Emitting Plant

Abstract: The engineering of living plants for visible light emission and sustainable illumination is compelling because plants possess independent energy generation and storage mechanisms and autonomous self-repair. Herein, we demonstrate a plant nanobionic approach that enables exceptional luminosity and lifetime utilizing four chemically interacting nanoparticles, including firefly luciferase conjugated silica (SNP-Luc), D-luciferin releasing poly(lactic-co-glycolic acid) (PLGA-LH 2 ), coenzyme A functionalized chito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 32 publications
(58 reference statements)
0
93
0
Order By: Relevance
“…Preparation of SNP‐AF488 : SNP‐AF488 was prepared as previously described . Briefly, (3‐glycidyloxypropyl)trimethoxysilane (GPTS) was added to a mixture of 75% ethanol/water and incubated at room temperature for 1 h for complete hydrolysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preparation of SNP‐AF488 : SNP‐AF488 was prepared as previously described . Briefly, (3‐glycidyloxypropyl)trimethoxysilane (GPTS) was added to a mixture of 75% ethanol/water and incubated at room temperature for 1 h for complete hydrolysis.…”
Section: Methodsmentioning
confidence: 99%
“…Besides nucleic acids, nanoparticles can also be functionalized with molecules such as fluorescent dyes for intracellular labeling in plants, active molecules for tracking and sensing purposes, and agrochemicals for crop health . Targeted delivery of nanoparticles to certain regions of plant tissue is also important for the creation of biomimetic systems such as light‐harvesting apparatuses, photonic devices, emission sources for near‐infrared communication to electronic devices, and carbon‐negative temperature and environmental sensors . We have previously shown that highly charged nanoceria, a nanoparticle‐based reactive oxygen species (ROS) scavenger, and certain polymer‐wrapped single‐wrapped carbon nanotubes (SWNTs) localized within the chloroplasts when introduced to plant mesophyll tissue, enabling photosynthetic rate augmentation and extending the photoactive lifetime of extracted chloroplasts .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid explosion of materials research and nanotechnology in the past few decades has recently allowed us to explore alternative strategies for enhancing existing, or enabling completely new, functions within biological systems. With careful material design and construction, many synthetic materials have been successfully coupled with biological systems, demonstrating new extrinsic functional properties that surpass many existing natural capabilities of biosystems, such as the adaptation to fatal environments (9)(10)(11), the ability to prolong life cycles (12), and photosynthesis in nonphotosynthetic species (13). Biological species have gone through millions of years of evolution to achieve many of their biofunctionalities; however, given the amazing compositional and structural diversity of advanced synthetic materials, it is expected that strategies for the integration of functional synthetic materials with biological systems for the design and engineering of nanobiohybrids are a more rapid, powerful, and costeffective alternative than natural evolution or genetic engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanoparticles also allowed for the reduction of the effective concentration of luciferin molecule inside plants below its critical toxic level of 300 × 10 −6 m . Demonstration of this plant nanobionic approach with a watercress ( Nasturtium officinale ) plant led to a record plant brightness of 1.44 × 10 12 photons per second or 50% of 1 µW commercial luminescent diode . The concept of light‐emitting plants as self‐powered, persistent photonic sources for illumination of a book was also demonstrated (Figure b).…”
Section: Energy Generation From Plantsmentioning
confidence: 99%